Metaphors and comparisons as a means of rethinking the phenomena of the surrounding world - Mustafa, Yusra Akram (Al-Adab Journal, 2022)
The article characterizes metaphors and comparisons as a means of rethinking the phenomena of the surrounding world; two directions are named within which metaphors and comparisons are studied: 1) the linguo-classification direction combines several classifications of metaphors and comparisons, which are basically focused on comparing two denotations through the meanings of word forms that are part of the trope; 2) the theoretical and conceptual direction is associated with the concept of conceptual displacement and is the basis of the theoretical and methodological study of metaphor and comparison, i.e. the modern theory of metaphor is being formed; The main attention is focused on the comparative concept of Aristotle, which postulates that a metaphor is a hidden comparison, that is, a metaphorical statement is based on a comparison or similarity of two or more objects.